Eupolauridine alkaloids of Polyalthia nemoralis - Minh Hang, Nguyen Thi; Tu Oanh, Nguyen Thi; Hue, Cao Thi; Tung, To Hai; Thoa, Ha Thi; Thanh, Le Nguyen; Giap, Tran Huu; Dung, Nguyen Anh; Hung, Nguyen Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Two eupolauridine alkaloids, eupolauridine (1) and 8-methoxyeupolauridine (2), together with a phenanthrene compound, 2,7-dihydroxy-3,6-dimethoxyphenanthrene (3), were isolated from the ethyl acetate extract of Polyalthia nemoralis barks. Their structures were elucidated on the basis of spectroscopic analysis and comparison with related known compounds. These compounds were evaluated the cytotoxicity on seven human cancer cell lines including KB, MCF7, LU-1, HepG2, LNCap, SW626 and SW480